2012
DOI: 10.2223/jped.2212
|View full text |Cite
|
Sign up to set email alerts
|

Limb abnormalities on trisomy 18: evidences for early diagnosis

Abstract: Objective: To assess the frequency and types of limb abnormalities observed among patients with trisomy 18, or Edwards syndrome (ES). Method:The sample consisted of consecutive patients evaluated by a clinical genetics service in the period from 1975 to 2008. The results of the cytogenetic analysis, as well as the clinical data were retrieved from the medical records, with special attention to limb abnormalities findings. All the karyotype analysis was performed at the same laboratory.Results: During the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(16 reference statements)
1
3
0
Order By: Relevance
“…The main alteration is the clenched fist with overlapping fingers, a finding that usually leads to the suspicion of the syndrome. Radial abnormalities, as observed in our case, are less common, seen in about 22% of patients [Rosa et al, ].…”
Section: To the Editorsupporting
confidence: 56%
“…The main alteration is the clenched fist with overlapping fingers, a finding that usually leads to the suspicion of the syndrome. Radial abnormalities, as observed in our case, are less common, seen in about 22% of patients [Rosa et al, ].…”
Section: To the Editorsupporting
confidence: 56%
“…In comparison with previously reported cases due to MED12 R296Q ( Caro-Llopis et al, 2016 ; Martínez et al, 2017 ; Rocchetti et al, 2021 ) and clinical features summarized by Plassche and Brouwer (2021) , the pattern of fetal clenched hand with overlapping fingers and clubfoot is reported for the first time in our study. However, among the types of fetal hand and foot abnormalities, overlapping fetus fingers are characteristic phenotypes of fetuses carrying aneuploidy, such as trisomies 18, 13, and 21 ( Witters et al, 2011 ; Rosa et al, 2012 ), which are usually diagnosed by prenatal chromosome screening. Clinicians are often unable to provide clear decision-making advice when chromosome results are unclear, such as low-risk NIPT results or karyotype analysis is negative.…”
Section: Discussionmentioning
confidence: 99%
“…13 Mortality in patients with trisomy 18 is mostly due to respiratory or heart failure, although recent studies found little or no association of congenital heart defects with survival rate. 14 Our patient was referred at the age of 4 months, where the survival rate varies between 3 to 23 percent based on studies from different countries. 15 A multi-state population-based study recently revealed gestational age as the strongest predictor of mortality, with highest 1-month and 1-year survival probabilities of trisomy 18 infants born at full term (48.8 and 17.2 percent, respectively).…”
Section: Discussionmentioning
confidence: 99%